Llama, Llama Red Pajama - Dewdney, Anna (New York : Viking, 2005)
At bedtime, a little llama worries after his mother puts him to bed and goes downstairs.
Ages 2 up.
Keywords: Mother-child relationship -- Fiction; Bedtime -- Fiction; Llamas -- Fiction; Stories in rhyme